Basel III and the Technical Challenge for Bank Liquidity Risk Management. Issue 72 (July 2014) - Choudhry, Moorad
Abstract Genuine liquidity crises are rare. This may explain why over time some banks relax traditional liquidity principles and run riskier funding regimes. The experience of Northern Rock in 2007 illustrates what can happen when a conservative approach to funding is abandoned. The response of regulators to the crash of 2008 was "Basel III", which raises the level of capital that banks must maintain, but also dictates new minimum standards for liquidity adequacy. The calculation of the Basel III liquidity ratios themselves is straightforward. However, a proper understanding of the metrics requires an awareness of definitions and assumptions for both assets and liabilities, and an appreciation of how they behave in practice. This is the real challenge of Basel III that is explored in this article.